Immune responses to SARS-CoV-2 vaccines in celiac disease. (1st February 2023) - Ibsen, Jostein H.; Chopra, Adity; Vaage, Eline Benno; Vaage, John T.; Lund-Johansen, Fridtjof; Lundin, Knut E. A.
Abstract: Background and aims: SARS-CoV-2 infection and development of the disease COVID-19 is a serious threat to our society. Effective vaccines have now entered the market, but most patient populations were not included in the registration clinical trials. There is evidence that patients with celiac disease (CeD) have reduced effect of vaccines such as the hepatitis B vaccine. Hence, we investigated the humoral response to SARS-CoV-2 vaccines (Chadox1, Comirnaty and Spikevax) in CeD patients and healthy controls. Methods: CeD patients from a patient registry at Oslo University Hospital were invited to donate serum samples before and after vaccination. We sent out 1537 invitations and received paired samples from 85 individuals. These were compared with similar samples from 238 healthy controls. Sera were analyzed for antibodies to the Spike protein from SARS-CoV2 and the receptor-binding domain. The results where then converted into binding antibody units (BAU)/ml to compare. Results: Prevaccination samples showed that very few patients had been earlier exposed to Sars-CoV2 and the antibody levels were low. Postvaccination analysis showed overlap of antibody levels between CeD and healthy controls. On average, the CeD patient group had 5555.0 BAU/ml (330.1 SD) while the average in healthy controls was 5419 (184.7 SD). Conclusion: The humoral response to SARS-CoV-2 vaccines in CeD patients is similar to that observed in healthy controls. Graphical Abstract: UF0001 (Created with BioRender.com)